Perceived challenges in delivering comprehensive care for patients following stroke: a qualitative study of stroke care providers in Guangdong Province, China. Issue 1 (11th January 2022) - Wu, Chanchan; Zou, Guanyang; Chen, Minjie; Wan, Lihong; Kielmann, Karina; McCormack, Brendan
Abstract: Purpose: To understand the challenges in delivering comprehensive care for patients recovering from stroke in Guangdong Province, China. Methods: A cross-sectional qualitative study was conducted in two tertiary hospitals with different socio-economic characteristics in Guangdong Province, Southern China. Interviews were conducted with 16 stroke care providers including doctors, nurses, rehabilitation therapists and care workers. The interviews were audiotaped, transcribed and translated from Mandarin to English. Thematic analysis was used to draw out descriptive and analytical themes relating to care providers' experiences of existing routine stroke care services and the perceptions of challenges in delivering comprehensive stroke care. Results: The interviews with stroke care providers highlighted three key factors that hinder the capacity of the two hospitals to deliver comprehensive stroke care. First, expertise and knowledge regarding stroke and stroke care are lacking among both providers and patients; second, stroke care systems are not fully integrated, with inadequate coordination of the stroke team and inconsistency in care following discharge of stroke patients; third, stroke patients have insufficient social support. Conclusions: While comprehensive stroke care has become a priority in China, our study highlights some important gaps in the current provision of stroke care. IMPLICATIONS FOR REHABILITATION: Comprehensive integrated stroke care is essential to maximize the effectiveness of stroke services and in China it needs to be further improved. Multidisciplinary stroke care systems should strengthen collaborations across all relevant disciplines and should include a clear role for registered nurses. Follow-up care after discharge needs more engagement with family caregivers.